Battery solid electrolyte and preparation method thereof, diaphragm and secondary battery
By using LiMyQ2-y(PO4)3 material with NASICON structure in the battery to coat the core, the problem of unstability of LATP material to the negative electrode is solved, the stability and cycling performance of the solid electrolyte of the battery is improved, the conductivity decrease is avoided, and the improvement of the improvement of the performance of the battery is improved. The overall performance of the battery.
Patent Information
- Application Number
- CN202411358917.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In traditional batteries, LATP materials are unstable to the negative electrode and are prone to react with active lithium, resulting in a decrease in the first-effect and cycling performance of the battery and a low ionic conductivity.
The core is coated with LiMyQ2-y(PO4)3 material with NASICON structure. The compound valence of M and Q elements is stable, avoiding reaction with the negative electrode, expanding the selection range of A and T elements in the core material, and forming a stable coating layer. , improve the stability of the battery solid electrolyte.
Effectively isolate the reaction between the core and the negative electrode or active lithium, improve the first-term effect and cycling performance of the battery, and avoid the decrease in ionic conductivity.
Smart Images

Figure CN119263243A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a solid electrolyte for batteries, a method for preparing the same, a separator, and a secondary battery. Background Technology
[0002] In traditional techniques, LATP (e.g., Li) is used. 1.4 Al 0.4 Ti 1.6 (PO4)3) is applied as a coating to the battery separator to enhance ion conduction, improve battery performance, thermal stability, cycle performance, and safety, and extend battery life. However, during battery formation, LATP is unstable at the negative electrode and can react with active lithium, reducing the battery's initial efficiency and cycle performance. Summary of the Invention
[0003] Based on this, one embodiment of this application provides a battery solid electrolyte and its preparation method, a separator, and a secondary battery to improve the stability of the battery solid electrolyte, thereby improving the battery's first efficiency and cycle performance.
[0004] In a first aspect, this application provides a battery solid electrolyte, the battery solid electrolyte comprising a core and a coating layer covering at least a portion of the surface of the core; the core comprises a compound with the chemical formula Li 1+x A x T 2-x The material is (PO4)3, wherein the element A includes at least one of Al and Ga, the element T includes at least one of Ti and Ge, and 0.1 ≤ x ≤ 0.8.
[0005] The coating layer contains LiM y Q 2-y The material is (PO4)3, wherein the M element includes at least one of Al, Mg, Sc, In and La, the Q element includes at least one of Zr and Hf, and 0≤y≤0.5.
[0006] In some implementations, the overlay completely covers the surface of the core.
[0007] In some embodiments, the volume average particle size Dv50 of the kernel is 0.3 μm to 1.5 μm.
[0008] In some embodiments, the thickness of the coating layer is 10 nm to 150 nm.
[0009] Secondly, this application provides a method for preparing a solid electrolyte for a battery, the method comprising:
[0010] A first lithium source, a compound containing element A, a compound containing element T, and a first phosphorus source are mixed and subjected to a first sintering process to obtain a core, wherein the core contains a compound with the chemical formula Li. 1+x A x T 2-x The material is (PO4)3, wherein the element A includes at least one of Al and Ga, the element T includes at least one of Ti and Ge, and 0.1 ≤ x ≤ 0.8;
[0011] The core and a coating material are mixed, the coating material comprising a second lithium source, a compound containing element M, a compound containing element Q, and a second phosphorus source. After a second sintering, a coating layer is formed on at least a portion of the surface of the core, the coating layer comprising the chemical formula LiM. y Q 2-y The material is (PO4)3, wherein the M element includes at least one of Al, Mg, Sc, In and La, the Q element includes at least one of Zr and Hf, and 0≤y≤0.5.
[0012] In some embodiments, the first sintering temperature is 900℃~1000℃, the time is 6h~10h, and the atmosphere is a protective atmosphere.
[0013] In some embodiments, the second sintering temperature is 900℃~1000℃, the time is 10h~15h, and the atmosphere is a protective atmosphere.
[0014] Thirdly, this application provides a separator, the separator comprising a separator substrate and a solid electrolyte layer disposed on at least one surface of the separator substrate, the solid electrolyte layer being made of at least one of the battery solid electrolytes as described in the first aspect and battery solid electrolytes prepared by the preparation method described in the second aspect.
[0015] In some embodiments, the thickness of the diaphragm substrate is 5 μm to 12 μm, and the porosity is 41% to 49%.
[0016] In some embodiments, the thickness of the solid electrolyte layer is 1 μm to 5 μm, and the coating surface density is 3.4 g / m². 2 ~5.0g / m 2 .
[0017] In some embodiments, the diaphragm further includes a ceramic layer disposed on the side of the diaphragm substrate away from the solid electrolyte layer.
[0018] Optionally, the thickness of the ceramic layer is 1 μm to 5 μm, and the coating density is 3.1 g / m². 2 ~5.1g / m 2 .
[0019] In some embodiments, the diaphragm further includes an adhesive layer disposed on the side of the solid electrolyte layer away from the diaphragm substrate.
[0020] Optionally, the thickness of the adhesive coating layer is 1μm to 3μm, and the coating surface density is 0.3g / m³. 2 ~0.9g / m 2 .
[0021] Fourthly, this application provides a secondary battery, the secondary battery comprising the separator as described in the third aspect.
[0022] Compared with traditional technologies, this application has at least the following beneficial effects:
[0023] This application utilizes LiM with a NASICON structure. y Q 2-y The (PO4)3 material coating core, in which the oxidation states of M and Q elements are stable and do not react with the negative electrode, effectively isolates the core material from the reaction between the core material and the negative electrode or active lithium, and expands the selection range of A and T elements in the core material. This application effectively improves the stability of the battery solid electrolyte, avoids the problem of decreased ionic conductivity caused by the reaction between the core battery solid electrolyte and active lithium, thereby improving the battery's initial efficiency and cycle performance. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the structure of a solid electrolyte for a battery provided in one embodiment of this application; wherein, 1-core, 2-coating layer.
[0025] Figure 2 This is a schematic diagram of the structure of a diaphragm provided in one embodiment of this application; wherein, 10-diaphragm; 11-diaphragm substrate; 12-solid electrolyte layer; 13-ceramic layer; 14-coating layer.
[0026] Figure 3 This is a SEM image of the solid electrolyte for the battery prepared in Example 1 of this application.
[0027] Figure 4 This is a comparison chart of the capacity retention test results during the cycling process of Example 1 and Comparative Example 1 of this application. Detailed Implementation
[0028] The present application will be further described in detail below with reference to the embodiments and examples. These embodiments and examples are only for illustrating the present application and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. In addition, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0030] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0031] In this application, the terms "first aspect," "second aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first aspect," "second aspect," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0032] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0033] In this application, when numerical intervals (i.e., numerical ranges) are mentioned, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0034] All references to this application are incorporated herein by reference as if each document were individually incorporated herein by reference. Unless they conflict with the purpose and / or technical solution of this application, all cited references are incorporated herein by reference in their entirety and for all purposes. When references are cited in this application, the definitions of relevant technical features, terms, nouns, phrases, etc., are also incorporated herein by reference. Examples and preferred embodiments of the cited technical features may also be incorporated herein by reference, but only to the extent that they enable the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, this application shall prevail or modifications shall be made adaptably to the description in this application.
[0035] LATP materials (e.g., Li) 1.4 Al 0.4 Ti 1.6 (PO4)3) During battery formation, the LATP layer forms a film together with the negative electrode surface, consuming active lithium and reducing the battery's initial efficiency. Furthermore, the LATP layer is unstable to the negative electrode; as the battery is used, the Ti in the coating... 4+ It will gradually revert to Ti 2+ The closer to the interior of the coating, the better the Ti content. 2+ Higher Fe content accelerates battery cycle capacity loss; moreover, the low porosity of the LATP layer leads to increased membrane impedance. Traditional technologies utilize trivalent Fe cations... 3+ and Gr 3+ Doping can improve the ionic conductivity of solid electrolytes and reduce the reaction between Li metal and LATP materials, but after doping, the reaction with Ti during cycling will increase. 4+ It will still gradually revert to Ti 2+This leads to a loss of cycle capacity. In addition, traditional technologies also use boron nitride to coat LATP material, which reacts with lithium metal to generate Li3N, isolating LATP from the lithium metal anode. However, this still consumes some lithium, affecting the battery's cycle performance.
[0036] The first aspect of this application provides a battery solid electrolyte, such as... Figure 1 As shown, the battery solid electrolyte includes a core 1 and a coating layer 2 covering at least a portion of the surface of the core 1; the core 1 contains Li 1+ x A x T 2-x The material is (PO4)3, wherein the element A includes at least one of Al and Ga, the element T includes at least one of Ti and Ge, and 0.1 ≤ x ≤ 0.8.
[0037] The coating layer 2 contains LiM y Q 2-y The material is (PO4)3, wherein the M element includes at least one of Al, Mg, Sc, In and La, the Q element includes at least one of Zr and Hf (hafnium), and 0≤y≤0.5.
[0038] This application utilizes LiM with a NASICON structure. y Q 2-y The (PO4)3 material coating core, in which the oxidation states of M and Q elements are stable and do not react with the negative electrode, effectively isolates the core material from the reaction between the core material and the negative electrode or active lithium, and expands the selection range of A and T elements in the core material. This application effectively improves the stability of the battery's solid-state electrolyte, avoids the problem of decreased ionic conductivity caused by the reaction between the core battery's solid-state electrolyte and active lithium, thereby improving the battery's initial efficiency and cycle performance.
[0039] Where x includes, but is not limited to: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8. y includes, but is not limited to: 0, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, or 0.50. For example, the kernel contains Li. 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and Li 1.8 Al 0.2 Ti1.2 The coating layer comprises at least one of (PO4)3. 0.5 Zr 1.5 At least one of (PO4)3.
[0040] In some embodiments, the coating layer completely covers the surface of the core. This application utilizes a coating layer to completely cover the core, thereby completely preventing the core from reacting with the negative electrode material.
[0041] In some embodiments, the volume average particle size Dv50 of the kernel is 0.3 μm to 1.5 μm, for example, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm.
[0042] In some embodiments, the thickness of the coating layer is 10nm to 150nm, for example, it can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 880nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, or 150nm. This application selects the core particle size and coating layer thickness as described above to ensure the stability of the battery's solid-state electrolyte and avoid excessively low ionic conductivity of the material.
[0043] A second aspect of this application provides a method for preparing a solid electrolyte for a battery, the method comprising:
[0044] A first lithium source, a compound containing element A, a compound containing element T, and a first phosphorus source are mixed and subjected to a first sintering process to obtain a core, wherein the core contains a compound with the chemical formula Li. 1+x A x T 2-x The material is (PO4)3, wherein the element A includes at least one of Al and Ga, the element T includes at least one of Ti and Ge, and 0.1 ≤ x ≤ 0.8;
[0045] The core and a coating material are mixed, the coating material comprising a second lithium source, a compound containing element M, a compound containing element Q, and a second phosphorus source. After a second sintering, a coating layer is formed on at least a portion of the surface of the core, the coating layer comprising the chemical formula LiM. y Q 2-y The material is (PO4)3, wherein the M element includes at least one of Al, Mg, Sc, In and La, the Q element includes at least one of Zr and Hf, and 0≤y≤0.5.
[0046] The above method for preparing solid-state electrolytes for batteries is simple and provides good coating effects. The resulting solid-state electrolyte utilizes LiMnO4 with a NASICON structure. y Q 2-y The (PO4)3 material coating core, in which the oxidation states of M and Q elements are stable and do not react with the negative electrode, effectively isolates the core material from the reaction between the core material and the negative electrode or active lithium, and expands the selection range of A and T elements in the core material. This application effectively improves the stability of the battery solid electrolyte, avoids the problem of decreased ionic conductivity caused by the reaction between the core battery solid electrolyte and active lithium, thereby improving the battery's initial efficiency and cycle performance.
[0047] In some embodiments, the first sintering temperature is 900℃~1000℃, for example, it can be 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃, or 1000℃. The selection of the first sintering temperature as described above effectively ensures sufficient reaction of the raw materials and avoids impurities in the core material. For example, taking LATP as the core material, when the temperature is relatively low, the raw material reaction is insufficient, and some raw materials may remain in the LATP, affecting the material properties; when the temperature is relatively high, LATP may decompose, resulting in impurities such as Li3PO4 and AlPO4.
[0048] In some embodiments, the first sintering time is 6h to 10h, for example, it can be 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 9.0h, 9.5h or 10.0h.
[0049] In some embodiments, the atmosphere for the first sintering is a protective atmosphere. It is understood that a protective atmosphere refers to a gas that does not react with the raw materials; it can be an inert gas or other gases, such as argon. Optionally, the atmosphere for the first sintering in this application is a flowing protective atmosphere, which carries away the gases generated during the reaction process. For example, if carbonates or ammonia nitrogen salts are used in the raw materials, the protective atmosphere is used to purge and carry away the generated carbon dioxide and ammonia.
[0050] In some embodiments, the preparation method further includes: crushing the core obtained after the first sintering. Optionally, the volume average particle size Dv50 of the crushed core is 0.3 μm to 1.5 μm. The selection of the volume average particle size of the core as described above in this application can improve the stability of the prepared solid electrolyte.
[0051] In some embodiments, the second sintering temperature is 900℃~1000℃, for example, it can be 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃ or 1000℃. The above-mentioned selection of the second sintering temperature in this application avoids the decomposition of raw materials and the generation of impurities (e.g., the generation of Li3PO4 and AlPO4 impurities), and can also improve the coating stability of the prepared battery solid electrolyte.
[0052] In some embodiments, the second sintering time is 10h to 15h, for example, it can be 10.0h, 10.5h, 11.0h, 11.5h, 12.0h, 12.5h, 13.0h, 13.5h, 14.0h, 14.5h or 15.0h.
[0053] In some embodiments, the atmosphere for the second sintering is a protective atmosphere.
[0054] In some embodiments, the first lithium source and the second lithium source each independently include at least one of lithium carbonate, lithium hydroxide, and lithium nitrate.
[0055] In some embodiments, the first phosphorus source and the second phosphorus source each independently comprise at least one of ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
[0056] In some embodiments, the compound containing element A can be at least one of oxides, carbonates, chlorides, fluorides, and hydroxides containing element A. For example, when element A is Al, the compound containing element A can be Al₂O₃.
[0057] In some embodiments, the compound containing element T can be at least one of oxides, carbonates, fluorides, and hydroxides containing element T. For example, when element T is Ti, the compound containing element T can be TiO2.
[0058] In some embodiments, the compound containing element M can be at least one of oxides, carbonates, fluorides, and hydroxides containing element M. For example, when element M is Mg, the compound containing element M can be MgO.
[0059] In some embodiments, the compound containing element Q can be at least one of oxides, carbonates, fluorides, and hydroxides containing element Q. For example, when element Q is Zr, the compound containing element M can be ZrO2.
[0060] In some embodiments, the molar ratio of lithium in the first lithium source, A in the compound containing A, T in the compound containing T, and phosphorus in the first phosphorus source is (1.2~2.35):(0.1~0.8):(1.2~1.9):3.
[0061] In some embodiments, the molar ratio of lithium in the second lithium source, M in the compound containing M, Q in the compound containing Q, and phosphorus in the second phosphorus source is 1:(0~0.5):(1.5~2):3.
[0062] In some embodiments, the mass ratio of the core to the coating material is (1.2~5000):1, for example, it can be 1.2:1, 5:1, 10:1, 50:1, 100:1, 500:1, 1000:1, 1500:1, 2000:1, 2500:1, 3000:1, 3500:1, 4000:1, 4500:1, or 5000:1. This application selects the mass ratio between the core and the coating material as described above to ensure the coating effect and the thickness of the coating layer, thereby effectively improving the stability of the battery's solid electrolyte.
[0063] Exemplarily, a method for preparing the above-mentioned solid electrolyte for batteries is provided, comprising the following steps:
[0064] S1. Weigh the first lithium source, the compound containing element A, the compound containing element T, and the first phosphorus source according to the elemental molar ratio. Mix them evenly and then perform a first sintering at 900℃~1000℃ for 6h~10h. A protective atmosphere is used during sintering. After crushing, the resulting product contains the chemical formula Li. 1+x A x T 2-x The core of (PO4)3 has a volume average particle size Dv50 of 0.3 μm to 1.5 μm.
[0065] S2. Weigh the core and coating material prepared in S1. The coating material includes a second lithium source, a compound containing element M, a compound containing element Q, and a second phosphorus source. After mixing them evenly, perform a second sintering at 900℃~1000℃ for 10h~15h. A protective atmosphere is used during sintering. A coating layer with a thickness of 10nm~150nm is formed on at least a portion of the surface of the core. The coating layer contains a compound with the chemical formula LiM. y Q 2-y (PO4)3 material was crushed to obtain a modified solid electrolyte for batteries.
[0066] A third aspect of this application provides a diaphragm, such as Figure 2As shown, the separator 10 includes a separator substrate 11 and a solid electrolyte layer 12 disposed on at least one side surface of the separator substrate 11. The material of the solid electrolyte layer 12 includes at least one of the battery solid electrolyte as described in the first aspect and the battery solid electrolyte prepared by the preparation method described in the second aspect.
[0067] It is understood that the solid electrolyte layer in the above-described separator includes a battery solid electrolyte, a binder, and other functional additives. The battery solid electrolyte includes at least one of the above-described battery solid electrolyte and the battery solid electrolyte prepared by the above-described preparation method. The binder and other functional additives can be materials commonly used in this technical field.
[0068] In some embodiments, the material of the diaphragm substrate includes at least one of polyethylene and polypropylene.
[0069] In some embodiments, the thickness of the diaphragm substrate is 5μm to 12μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm.
[0070] In some embodiments, the porosity of the diaphragm substrate is 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, or 49%.
[0071] In some embodiments, the thickness of the solid electrolyte layer is 1 μm to 5 μm, for example, it can be 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm.
[0072] In some embodiments, the coating surface density of the solid electrolyte layer is 3.4 g / m². 2 ~5.0g / m 2 For example, it could be 3.4g / m 2 3.5g / m 2 3.6g / m 2 3.7g / m 2 3.8g / m 2 3.9g / m 2 4.0g / m 2 4.1g / m 2 4.2g / m 2 4.3g / m 2 4.4g / m 2 4.5g / m 2 4.6g / m 2 4.7g / m 2 4.8g / m 2 4.9g / m2 Or 5.0g / m 2 .
[0073] In some embodiments, such as Figure 2 As shown, the diaphragm 10 further includes a ceramic layer 13, which is disposed on the side of the diaphragm substrate 11 away from the solid electrolyte layer 12.
[0074] Optionally, the thickness of the ceramic layer is 1μm to 5μm, for example, it can be 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm or 5.0μm.
[0075] Optionally, the surface density of the ceramic layer is 3.1 g / m³. 2 ~5.1g / m 2 For example, it could be 3.1g / m 2 3.3g / m 2 3.5g / m 2 3.7g / m 2 3.9g / m 2 4.1g / m 2 4.3g / m 2 4.5g / m 2 4.7g / m 2 4.9g / m 2 Or 5.0g / m 2 .
[0076] Optionally, the material of the ceramic layer includes AlOOH.
[0077] In some embodiments, such as Figure 2 As shown, the diaphragm 10 further includes an adhesive layer 14, which is disposed on the side of the solid electrolyte layer 12 away from the diaphragm substrate 11.
[0078] Optionally, the thickness of the adhesive coating layer is 1μm to 3μm, for example, it can be 1.0μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm or 3.0μm.
[0079] Optionally, the surface density of the adhesive coating layer is 0.3 g / m³. 2 ~0.9g / m 2 For example, it could be 0.3g / m 2 0.4g / m 2 0.5g / m 2 0.6g / m 2 0.7g / m 20.8g / m 2 or 0.9g / m 2 .
[0080] Optionally, the material of the adhesive layer includes polyvinylidene fluoride (PVDF).
[0081] A fourth aspect of this application provides a secondary battery comprising a separator as described in the third aspect.
[0082] The aforementioned secondary battery may include, for example, the separator, positive electrode, negative electrode, and electrolyte described in this application. The separator is disposed between the positive and negative electrodes, primarily serving to prevent short circuits between the positive and negative electrodes, while simultaneously allowing active ions to pass through. The electrolyte, located between the positive and negative electrodes, serves to conduct active ions. During the charging and discharging process of the secondary battery, active ions repeatedly insert and extract between the positive and negative electrodes. This application does not impose any particular limitations on the positive electrode, negative electrode, and electrolyte; the positive electrode, negative electrode, and electrolyte can be prepared using methods commonly used in this technical field, or commonly used positive electrode, negative electrode, and electrolyte in this art. Optionally, the aforementioned secondary battery includes a lithium-ion battery.
[0083] In some embodiments, the separator includes a ceramic layer, a separator substrate, a solid electrolyte layer and an adhesive layer stacked sequentially, with the side of the separator having the solid electrolyte layer facing the negative electrode in the battery.
[0084] Furthermore, another embodiment of this application provides an electrical device including the secondary battery described above.
[0085] The aforementioned electrical devices may include any equipment or device powered by a secondary battery, such as mobile phones, laptops, electric vehicles, ships, satellites, energy storage devices, smart home appliances, etc., but are not limited thereto.
[0086] The embodiments of this application will be described in detail below with reference to examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0087] Example 1
[0088] S1. Lithium carbonate, aluminum oxide, titanium dioxide, and ammonium dihydrogen phosphate were weighed according to a molar ratio of 0.8:0.2:1.6:3, mixed and stirred evenly, and then subjected to a first sintering at 950℃ for 8 hours. The generated carbon dioxide and ammonia were removed by introducing argon gas. After crushing, a particle size with a volume average Dv50 of 0.9 μm and chemical formula Li was obtained. 1.4 Al 0.4 Ti 1.6 (PO4)3 kernel;
[0089] S2. Lithium carbonate, aluminum oxide, zirconium dioxide, and ammonium dihydrogen phosphate were weighed in a molar ratio of 0.5:0.25:1.5:3 to obtain the coating material. The core and coating material were weighed in a mass ratio of 1.21:1, mixed and stirred evenly, and then subjected to a second sintering at 950℃ for 12 hours in an argon atmosphere. The material formed by coating the surface of the core was LiAl. 0.5 Zr 1.5 A coating layer of (PO4)3 with a thickness of 100 nm was obtained after crushing. Figure 3 The battery shows a solid electrolyte.
[0090] This embodiment also provides a diaphragm, the preparation method of which includes:
[0091] A PE membrane substrate with a thickness of 9μm and a porosity of 45% is provided;
[0092] The coating solution containing the aforementioned battery solid electrolyte was coated onto the surface of a PE separator substrate at a coating density of 4.2 g / m³. 2 The solid electrolyte layer with a thickness of 3 μm was obtained by drying; then, PVDF (polyvinylidene fluoride) adhesive was coated on the solid electrolyte layer at a coating density of 0.6 g / m³. 2 The coating layer is dried to form a thickness of 1 μm.
[0093] An AlOOH ceramic slurry is also coated on the surface of the PE membrane substrate away from the solid electrolyte layer, with a coating density of 4 g / m³. 2 After drying, a ceramic layer with a thickness of 3 μm is obtained, and a diaphragm is prepared.
[0094] Example 2
[0095] S1. Lithium carbonate, aluminum oxide, germanium dioxide, and ammonium dihydrogen phosphate were weighed according to a molar ratio of 0.9:0.25:1.5:3, mixed and stirred evenly, and then subjected to a first sintering at 1000℃ for 6 hours. The generated carbon dioxide and ammonia were removed by introducing argon gas. After crushing, a volume average particle size Dv50 of 0.3 μm was obtained, with the chemical formula Li. 1.5 Al 0.5 Ge 1.5(PO4)3 kernel;
[0096] S2. Lithium carbonate, zirconium dioxide, and ammonium dihydrogen phosphate were weighed in a molar ratio of 0.5:2:3 to obtain a coating material. The core and coating material were weighed in a mass ratio of 4.68:1. After mixing and stirring evenly, a second sintering was carried out at 1000℃ for 10 hours in an argon atmosphere. A coating layer of LiZr2(PO4)3 was formed on the surface of the core with a thickness of 10 nm. After crushing, the solid electrolyte of the battery was obtained.
[0097] This embodiment also provides a diaphragm, which differs from the diaphragm preparation method in Example 1 only in that the thickness of the solid electrolyte layer is 1 μm and the coating surface density of the solid electrolyte layer is 3.4 g / m³. 2 .
[0098] Example 3
[0099] S1. Lithium carbonate, aluminum oxide, titanium dioxide, and ammonium dihydrogen phosphate were weighed according to a molar ratio of 1.1:0.4:1.2:3, mixed and stirred evenly, and then subjected to a first sintering at 900℃ for 10 hours. The generated carbon dioxide and ammonia were removed by introducing argon gas. After crushing, a volume average particle size Dv50 of 1.5 μm was obtained, with the chemical formula Li. 1.8 Al 0.8 Ti 1.2 (PO4)3 kernel;
[0100] S2. Lithium carbonate, magnesium oxide, zirconium dioxide, and ammonium dihydrogen phosphate were weighed in a molar ratio of 0.5:0.5:1.5:3 to obtain the coating material. The core and coating material were weighed in a mass ratio of 1.37:1, mixed and stirred evenly, and then subjected to a second sintering at 1000℃ for 10 hours in an argon atmosphere. The coating material formed on the surface of the core was LiMg. 0.5 Zr 1.5 The (PO4)3 coating layer has a thickness of 150 nm, and the solid electrolyte of the battery is obtained after crushing.
[0101] This embodiment also provides a diaphragm, which differs from the diaphragm preparation method in Example 1 only in that the thickness of the solid electrolyte layer is 5 μm and the coating surface density of the solid electrolyte layer is 5.0 g / m². 2 .
[0102] Example 4
[0103] The solid electrolyte for the battery was prepared according to the preparation method of Example 2, except that the core in step S1 was replaced with Li. 1.4 Al 0.4 Ti 1.6 (PO4)3.
[0104] Example 5
[0105] The solid electrolyte for the battery was prepared according to the preparation method of Example 2, except that the core in step S1 was replaced with Li. 1.8 Al 0.8 Ti 1.2 (PO4)3.
[0106] Example 6
[0107] The solid electrolyte for the battery was prepared according to the method of Example 1, except that in step S2, the mass ratio of the core to the coating material was 6000:1.
[0108] Example 7
[0109] The solid electrolyte for the battery was prepared according to the method of Example 1, except that in step S2, the mass ratio of the core material to the coating material was 1:1.
[0110] Example 8
[0111] The solid electrolyte for the battery was prepared according to the method of Example 1, except that in step S1, the average volumetric particle size Dv50 of the core after the crushing treatment was 0.2 μm.
[0112] Example 9
[0113] The solid electrolyte for the battery was prepared according to the method of Example 1, except that in step S1, the average volumetric particle size Dv50 of the core after the crushing treatment was 2 μm.
[0114] Example 10
[0115] The solid electrolyte for the battery was prepared according to the method of Example 1, except that the temperature of the second sintering treatment in step S2 was 850°C.
[0116] Example 11
[0117] The solid electrolyte for the battery was prepared according to the method of Example 1, except that the temperature of the second sintering treatment in step S2 was 1050°C.
[0118] Comparative Example 1
[0119] The Li prepared directly using step S1 in Example 1 1.4 Al 0.4 Ti 1.6 (PO4)3 is used as a solid electrolyte in batteries.
[0120] Comparative Example 2
[0121] The LiAl prepared directly using step S2 in Example 10.5 Zr 1.5 (PO4)3 is used as a solid electrolyte in batteries.
[0122] Comparative Example 3
[0123] The same PE membrane with the same thickness and porosity as that in Example 1 was used directly.
[0124] The composition of the solid electrolytes prepared in each embodiment and comparative example was determined using an ICP-AES (inductively coupled plasma atomic emission spectrometer).
[0125] The ionic conductivity of the solid electrolytes prepared in the above examples and comparative examples was tested using a BioLogic VSP-3E electrochemical workstation. The test results are shown in Table 1.
[0126] Assemble the separators prepared in the above embodiments and comparative examples into a secondary battery, including:
[0127] The positive electrode sheet is prepared according to the mass ratio of positive electrode material (LiFePO4): PVDF (polyvinylidene fluoride): conductive agent SP: CNTs (carbon nanotubes) = 97:2:0.5:0.5;
[0128] The negative electrode sheet is formulated according to the mass ratio of negative electrode material (graphite): CMC (carboxymethyl cellulose): conductive agent SP: SBR (styrene-butadiene rubber) = 96.5: 1: 0.5: 2.
[0129] The above-mentioned separator is assembled to form a 100Ah square aluminum-cased battery.
[0130] Performance testing, including:
[0131] The capacity retention rate of the secondary batteries prepared above was tested under the following conditions: room temperature (25℃), voltage 2.5V~3.65V, and capacity retention rate was tested at 0.5P / 0.5P. The test results are shown in Table 1. A comparison graph of the capacity retention rate test results during cycling of Example 1 and Comparative Example 1 is shown in the figure below. Figure 4 As shown.
[0132] Table 1
[0133]
[0134] As can be seen from the table above:
[0135] (1) Compared with Examples 6-7, Example 1 shows that the present application controls the coating amount of the coating layer, which effectively improves the stability of the solid electrolyte of the battery. However, the coating amount of Example 6 is less, which may not completely cover the core and cannot avoid Ti in the coating. 4+ It will gradually revert to Ti2+ The problem is that poor stability affects the cycle performance of the battery; while in Example 7, the coating amount is large, which may lead to an excessively thick coating layer. The ionic conductivity of the coating material is low, which will lead to a decrease in the overall ionic conductivity and affect the cycle performance of the battery.
[0136] (2) Compared with Examples 8-9, Example 1 shows that controlling the core particle size in this application can improve the stability of the prepared solid electrolyte. However, the core particle size in Example 8 is relatively small, which may cause a decrease in the ionic conductivity of the battery solid electrolyte, resulting in a decrease in battery capacity retention. In addition, due to the small core particle size, the crushing process is difficult, time-consuming, and energy-intensive. The core particle size in Example 9 is relatively large, which may be detrimental to the coating of the separator, making it impossible to obtain a smooth separator. It may also cause a decrease in the ionic conductivity of the battery solid electrolyte, resulting in a decrease in battery capacity retention.
[0137] (3) Compared with Examples 10-11, it can be seen that the present application controls the second sintering temperature, that is, the sintering temperature of the coating process, which effectively ensures the coating effect and does not introduce impurities. If the second sintering temperature is relatively low, it may lead to incomplete reaction and result in low ionic conductivity of the material; if the second sintering temperature is relatively high, it may cause Li on the surface of the material to be ablated, generating impurities, thereby reducing ionic conductivity.
[0138] (4) Compared with Comparative Examples 1-3, it can be seen that this application utilizes LiM with NASICON structure. y Q 2-y The (PO4)3 material coating core, in which the oxidation states of M and Q elements are stable and do not react with the negative electrode, effectively isolates the core material from the reaction between the core material and the negative electrode or active lithium, and expands the selection range of A and T elements in the core material. This application effectively improves the stability of the battery solid electrolyte, avoids the problem of decreased ionic conductivity caused by the reaction between the core battery solid electrolyte and active lithium, thereby improving the battery's initial efficiency and cycle performance.
[0139] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0140] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these modifications and improvements all fall within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the appended claims.
Claims
1. A battery solid electrolyte, characterized in that: The battery solid electrolyte comprises a core and a coating layer coated on at least a portion of the surface of the core; the core comprises a chemical formula of Li 1+x A x T 2-x (PO4)3 material, wherein the A element includes at least one of Al and Ga, the T element includes at least one of Ti and Ge, and 0.1≤x≤0.8; The coating layer comprises a chemical formula of LiM y Q 2-y (PO4)3 material, wherein the M element includes at least one of Al, Mg, Sc, In and La, the Q element includes at least one of Zr and Hf, and 0≤y≤0.
5.
2. The battery solid electrolyte according to claim 1, characterized in that The battery solid electrolyte meets at least one of the following conditions: (1) The coating layer completely covers the surface of the core; (2) The volume average particle size Dv50 of the core is 0.3 μm to 1.5 μm; (3) The coating layer has a thickness of 10 nm to 150 nm.
3. A method for preparing a solid electrolyte for a battery, characterized in that: The preparation method comprises: A first lithium source, a compound containing element A, a compound containing element T and a first phosphorus source are mixed, and a core is obtained after a first sintering. The core contains a chemical formula of Li 1+x A x T 2-x (PO4)3 material, wherein the A element includes at least one of Al and Ga, the T element includes at least one of Ti and Ge, and 0.1≤x≤0.8; The core and the coating material are mixed, wherein the coating material includes a second lithium source, a compound containing an M element, a compound containing an Q element, and a second phosphorus source, and a coating layer is formed on at least a portion of the surface of the core after a second sintering, wherein the coating layer includes a chemical formula of LiM y Q 2-y (PO4)3 material, wherein the M element includes at least one of Al, Mg, Sc, In and La, the Q element includes at least one of Zr and Hf, and 0≤y≤0.
5.
4. The preparation method according to claim 3, characterized in that: The first sintering is carried out at a temperature of 900° C. to 1000° C. for a time of 6 h to 10 h in a protective atmosphere.
5. The preparation method according to claim 3 or 4, characterized in that: The second sintering is performed at a temperature of 900° C. to 1000° C. for a time of 10 h to 15 h in a protective atmosphere.
6. A diaphragm, characterized in that: The diaphragm includes a diaphragm substrate and a solid electrolyte layer arranged on at least one side of the diaphragm substrate, and the material of the solid electrolyte layer includes at least one of the battery solid electrolyte described in any one of claims 1-2 and the battery solid electrolyte prepared by the preparation method described in any one of claims 3-5.
7. The diaphragm according to claim 6, characterized in that The solid electrolyte layer satisfies at least one of the following conditions: (1) The thickness of the diaphragm substrate is 5 μm to 12 μm, and the porosity is 41% to 49%; (2) The thickness of the solid electrolyte layer is 1 μm to 5 μm, and the coating surface density is 3.4 g / m 2 ~5.0g / m 2 .
8. The diaphragm according to claim 6 or 7, characterized in that The diaphragm further comprises a ceramic layer, and the ceramic layer is arranged on a side of the diaphragm substrate away from the solid electrolyte layer; Optionally, the thickness of the ceramic layer is 1 μm to 5 μm, and the coating surface density is 3.1 g / m 2 ~5.1g / m 2 .
9. The diaphragm according to claim 6 or 7, characterized in that: The diaphragm further comprises a coating layer, wherein the coating layer is arranged on a side of the solid electrolyte layer away from the diaphragm substrate; Optionally, the thickness of the coating layer is 1 μm to 3 μm, and the coating surface density is 0.3 g / m 2 ~0.9g / m 2 .
10. A secondary battery, characterized in that: The secondary battery comprises the separator according to any one of claims 6 to 9.